Current trends and prospects of tourism education and training in Greece - Moira, Polyxeni; Mylonopoulos, Dimitrios; Kefala, Stavroula (Piccola Impresa / Small Business, 2019)
Education and training have always been considered factors of utmost importance in economic development. To this aim, governments constantly strive to develop effective education systems, creating education and training structures at different levels which reflect the socio-economic conditions of each state. Since tourism as a social activity is internationally recognized as contributing significantly to economic and cultural development, the organization of the tourism education and training system is a research area of particular academic interest. More specifically, the structure of tourism education can be often confusing for both trainees and employers. This confusion is accentuated by factors such as the diversity of tourism as an interdisciplinary field and its inherent feature of employment seasonality, features directly linked to tourism enterprises, SME structure, function and employability opportunities. This article delves into the multidimensional system of tourism education and training in Greece, a country that is economically reliant on tourism. In particular, the education system is being analysed during the period of the country's economic crisis. Findings point out long-standing weaknesses of the education system intensified by uncoordinated political action under the pressure of the economic crisis. Analysis of tourism educational policy can possibly account for the ways knowledge is translated into practice, particularly in the area of small firms. This paper aspires to point out the relationship between government policy in Higher Education and small to medium sized enterprises (SMEs) by highlighting the importance of tourism education on local economy. It turns out that in Greece, tourism education and training suffers from inherent weaknesses that are not necessarily due to the economic crisis but are potentially exacerbated by it.